Normalization of Pervasive Developmental Disorder Screening Test - Mansoureh Karimzadeh; Ali Reza Baneshi; Mahnaz Dehghan Tezerjani; Zeynab Tayyebi Sough (University of Social Welfare and Rehabilitation Sciences, 2018)
Objective According to the Diagnostic and Statistical Manual of Psychiatric Disorders-Fifth Edition, Autism Spectrum Disorders (ASDs) are neurodevelopmental disorders associated with persistent defects in social communication and interactions, patterns, interests, behaviors, and repetitive and limited activities. In other words, ASDs are a lifelong condition characterized by widespread problems in social interaction and communication, stereotypical behaviors and limited interests. The early diagnosis of ASD can lead to early intervention and improvement of developmental outcomes. Parental screening tools are the ideal tools for the timely detection of ASD because they provide diagnostic information from the person familiar with the child and are easy to perform and score. This study aimed to standardize the Pervasive Developmental Disorder Screening Test (PDDST), which screens these disorders at an early age (12 to 48 months). This test consists of 36 questions that are answered as "Yes-No." Materials & Methods The population of this descriptive study included all children aged below 8 years with neurodevelopmental disorders and normal children of the same age group in Tehran. In relation to autistic children, the criteria for diagnosis were the persistent impairment of social communication and social interactions in different situations, and patterns of behavior and limited repetitive activities as assessed by a specialist and a psychiatrist. In relation to normal children, the inclusion criteria were the lack of these problems. Thus, a total of 252 children, i.e., 205 children with neurodevelopmental disorders (autism 135 and intellectual disability 70) and 47 normal children (to determine discriminant validity), were included as the sample for this study. Among them, 97 were girls and 157 were boys. The parents of the participants responded to screening tests within 10 minutes at the psychiatric clinics and hospitals in Tehran. The test validity through content by experts and the differential method with variance analysis technique, which shows the significance of the difference between the three groups of participants in the score obtained from the test, and the validity was calculated through the coefficient of internal consistency of Kuder-Richardson 20. Two criteria of validity (sensitivity and specificity) were used to determine the cutting point. Data analysis was performed using the SPSS V. 21 software. Results The content validity of the test was confirmed according to the experts' judgments. The results of discriminant validity revealed that there is a significant difference between groups (P=0.001). It was also found that the means of normal, intellectual disability, and autistic groups are, respectively, from the lowest to the highest. The reliability of the test was 0.73. The sensitivity of the child's screening for ASD is indicative of the accuracy of the screening of a child without ASD. The results of this study showed that the PDDST-II screening test for both sensitivity and specificity indices were in a favorable situation and could correctly identify children with autism and children without autistic dysfunction. The two sensitivity and specificity indicators in the score of 5 reached their highest, so the cut-off point for the test was scored at 5 and more.  Conclusion The results of this study showed that the psychometric properties of the PDDST-II screening test are suitable for discriminating between children with ASD and those with other developmental disorders such as mental retardation and normal children. This test also had a good reliability coefficient and is suitable for diagnosing children with ASD.